2006
DOI: 10.1002/cyto.b.20107
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric features of angioimmunoblastic T‐cell lymphoma

Abstract: Background: The immunophenotypic features of angioimmunoblastic T-cell lymphoma (AILT) have not been well described.Methods: We retrospectively reviewed our institutional experience with the flow cytometric features of 16 cases of AILT.Results: Multiparameter flow cytometry was able to identify a distinct population of immunophenotypically aberrant T cells in 15 of 16 cases. In 13 lymph node specimens, the neoplastic cells ranged from 1.9 to 87% (median 23%) of cells. The ratio of reactive to neoplastic T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…These authors also showed that this aberrant immunophenotype is exceedingly rare in other leukemic T-cell lymphomas and that detection of cells with this immunophenotype in PB had a 94 % positive predictive value for the diagnosis of AITL. The sCD3-/CD4+ immunophenotype in AITL has been shown previously by other investigators as well [7,20,21]. …”
Section: Discussionsupporting
confidence: 74%
“…These authors also showed that this aberrant immunophenotype is exceedingly rare in other leukemic T-cell lymphomas and that detection of cells with this immunophenotype in PB had a 94 % positive predictive value for the diagnosis of AITL. The sCD3-/CD4+ immunophenotype in AITL has been shown previously by other investigators as well [7,20,21]. …”
Section: Discussionsupporting
confidence: 74%
“…Unlike lymph nodes involved by AITL, using IHC, we also did not identify CD21+ or CD35+ FDCs in AITL infiltrates in BM. Our results, in large part, are consistent with what has been observed by other groups [17][18][19]27]. These results suggest that the immunophenotype of AITL is attributable, in large part, to its microenvironment, and therefore, immunophenotypic analysis is relatively less helpful for the workup of AITL in BM compared with lymph nodes.…”
Section: Discussionsupporting
confidence: 92%
“…Immunophenotypic aberrancies for T-cell-associated antigens (CD2, CD3, CD4, CD5, and CD7) and for CD45 have been reported previously, and our results confirm those findings (8)(9)(10)(11). Testing for CD94, CD161, and killer-cell immunoglobulin-like receptors was not helpful in our cases of AITL, in contrast to the diagnostic utility for clones of large granular lymphocytes in the blood (12).…”
Section: Vbeta Analysis By Flow Cytometry Is a New Techniquesupporting
confidence: 88%